Relationship Between Well-Being and Inclusive Practice in Chilean Teachers: A Preliminary Analysis - Villalta-Paucar, M (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Although numerous studies address inclusive education, especially in Latin America, research analyzing the overall life satisfaction of teachers in schools that implement inclusion policies are scarce. The purpose of this study is to analyze the relationship between Life Satisfaction, Optimism, Culture, and the Inclusive Practice of primary school teachers from Chile. A descriptive quantitative method was employed, with an ex post facto design including 246 primary teachers from urban and rural schools in Chile. The teachers completed four questionnaires: Inclusive Culture (IC), Inclusive Practice (IP) Satisfaction with Life Scale (SWSL), and Life Orientation Test Revised (LOT-R). The results show that these instruments present acceptable reliability. In addition, a significant correlation was found between Classroom Experience Time (CET) and SWSL (r = 0.201, p <.01), as well as between SWSL, and LOT-R (r = 0.411, p <.01), and IC and IP (r = 0.838, p <.01). The regression model is statistically significant [F (4, 241) = 139.572, p <.001]. The findings indicate that IC and SWSL predict IP directly, whereas CET is an inverse predictor. There is a statistically significant relationship between Life Satisfaction, Classroom Experience Time, Culture, and Inclusive Practice, with the three first variables being predictors of Inclusive Practice. © 2025 by the authors.